A Study on Data mining techniques used in Agriculture - Mondal, Biswajit (International Journal of Computer Sciences and Engineering, 2025)
Agriculture plays a vital role in India . Most of the people in India are involved for cultivation. This paper presents different techniques of data mining used in Agriculture sector. Several methodologies has been used in data mining techniques such as Neural Network, K-Means, Fuzzy-set , Bayesian Network, K-nearest neighbor, Decision tree analysis etc.